Hábitos alimentarios del pargo mancha Lutjanus guttatus (Pisces: Lutjanidae) en el Golfo de Nicoya, Costa Rica - Rojas M., José Rodrigo (1996)
A total of 504 "Spotted Snapper" Lutjanus guttatus were collected monthly in the Gulf of Nicoya, Costa Rica, from January 1993 to January 1994 to determine its feeding habits. The fishes studied ranged 12-620 cm in total length and were empty. Taking into account the whole sample, peneid shrimps were the most abundant taxon, they accounted for 59.3% of occurrence in the fish stomachs and 79.3% of the biomass. However, whereas the main food item in the stomach contents of juvenile fishes (smaller than 30 cm in total length) were peneids (Penaeus spp.) that of bigger fishes were stomatopods (Squilla spp.).